SISTEM PENDUKUNG KEPUTUSAN KETERCAPAIAN KOMPETENSI SISWA PADA SMA PLUS NEGERI 7 BENGKULU MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Farizal Sinambela; Herlina Latipa Sari (UNIVED Press, 2014)
The main purpose and the holding of this study was to create a Decision Support System Competency Achievement Plus Students at SMA Plus Negeri 7 Bengkulu Using Simple Additive Weighting Method (SAW). Data collection methods used in this study is the observation, interviews, and literature. Software used to build this system is Language Program-ming Visual Basic 6.0 and the results obtained are able to provide fast and precise output. The results of this study are in the form of Decision Support Systems Competency Achievement of SMA Plus Negeri 7 Bengkulu Using Simple Additive Weighting Method (SAW) which resulted in a decision that is the value of student learning outcomes. From the main menu there is a system consisting of data subjects, teacher data, student data, attendance data, the data value of cognitive, affective value funds, the data value of the practice, the data weights, the data input process of determining the complete-ness of data, and the menu contains a report which reports student learning outcomes and report student mastery achieve-ment. From the discussion, it can be concluded that Decision Support Systems Competency Achievement of SMA Plus Negeri 7 Bengkulu Using Simple Additive Weighting Method (SAW) replacing the old system with a new system which is a program that is specific.Keywords: Decision Support Systems, New Student Reception